MBRS-62. REPRESSIVE CHROMATIN REMODELERS IN SHH-DRIVEN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Tao, Rong-Hua; Dobson, Tara; Maegawa, Shinji; Swaminathan, Jyothismathi; Shaik, Shavali; Taylor, Pete; Kennis, Bridget; Qi, Lin; Khatua, Soumen; Goldman, Stewart; Lulla, Rishi; Fangusaro, Jason; et al.
Abstract: Medulloblastoma (MB) is a malignant pediatric brain tumor characterized by poor neuronal differentiation. The RE1 Silencing Transcription Factor (REST), which negatively regulates neurogenesis by promoting repressive chromatin remodeling via epigenetic modifications, is overexpressed in human MBs. Analyses of a publically available gene expression array data set revealed association of elevated REST expression in patients with Sonic Hedgehog (SHH) medulloblastoma with poor prognosis. Upon closer evaluation, we identified a subset of highly undifferentiated SHHα tumors with elevated REST expression and activity as determined by expression of REST target genes. These patients had an overall survival rate of 50% at 5 years. To understand the underlying mechanisms, we generated a novel mouse model expressing human REST transgene in a conditional manner in granule neural progenitors (GNPs), the cells of origin of SHH driven MB. Mice with constitutive activation of Shh signaling and REST elevation ( Ptch +/ - /REST TG ) in their GNPs developed tumors with a significant decrease in latency and increase in penetrance. We observed that 100% of Ptch +/ - /REST TG animals developed heterogeneously proliferative and undifferentiated tumors compared to tumor-bearing Ptch +/ - animals. Mechanistic studies revealed deregulation of the Shh signaling pathway by REST-dependent G9a activity, accompanied by loss of Ptch1 heterozygosity in Ptch +/ - /REST TG tumors. Thus, our studies suggest that REST contributes to mis-regulation of SHH activity and drives an aggressive disease course by deregulating proliferation and differentiation. Ours is also the first study to implicate G9a, a repressive chromatin remodeler, in medulloblastoma pathogenesis and as a potential therapeutic target.